2011
DOI: 10.1007/s11325-011-0573-2
|View full text |Cite
|
Sign up to set email alerts
|

Obstructive sleep apnea in epilepsy: a preliminary Egyptian study

Abstract: Sleep apnea is frequent in patients with epilepsy. OSA may contribute to increase seizure frequency. We recommend investigating sleep apnea in all patients with epilepsy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
16
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 19 publications
0
16
0
1
Order By: Relevance
“…The estimated prevalence of symptoms of OSA in CWE (55%) is of a similar order as that previously reported when using the same questionnaire tool. 17,21,22 A reverse association is also noted in the literature, with interictal epileptic discharges being found in 16.1% of children undergoing polysomnography for OSA, 29 and an increased incidence of epilepsy described in a cohort of young children with OSA. 1 The exact nature of the relation between epilepsy and OSA is unclear.…”
Section: Discussionmentioning
confidence: 73%
See 4 more Smart Citations
“…The estimated prevalence of symptoms of OSA in CWE (55%) is of a similar order as that previously reported when using the same questionnaire tool. 17,21,22 A reverse association is also noted in the literature, with interictal epileptic discharges being found in 16.1% of children undergoing polysomnography for OSA, 29 and an increased incidence of epilepsy described in a cohort of young children with OSA. 1 The exact nature of the relation between epilepsy and OSA is unclear.…”
Section: Discussionmentioning
confidence: 73%
“…Although there are small retrospective studies that have shown an increased OSA prevalence in sleep studies performed on CWE, 21,22 no prospective dataset has looked at this question. First, the numbers studied are small, with heterogeneity of epilepsy type within the group of CWE.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations